1996
DOI: 10.1002/(sici)1097-0215(19961009)68:2<207::aid-ijc12>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cells from human benign prostate hyperplasia produce a growth-inhibitory factor for LNCaP prostate cancer cells, identified as interleukin-6

Abstract: To understand specific interactions between stromal cells and epithelial cells in benign prostatic hyperplasia (BPH) and prostatic adenocarcinoma, we developed stromal-cell cultures from normal human prostate (PNX) and BPH (BH101), composed of fibroblasts and myofibroblasts. Their role in epithelial-cell growth was studied using the established cancer cell lines LNCaP, PC3 and DU145 and an SV40 large T-immortalized normal epithelial-cell line, PNT1A, in double-diffusion co-culture chambers. PNT1A was stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 30 publications
5
34
0
Order By: Relevance
“…However, the results presented here and those found previously (Lang et al, 1998) do not support this hypothesis. Our results, using a mixed population of stromal cells, would agree with both the theories that fibroblasts can stimulate (Kabalin et al, 1989;Gleave et al, 1991) or inhibit (Kooistra et al, 1995a;Degeorges et al, 1996) epithelial cell growth when compared to growth on tissue culture plastic. However, the majority of stromal cultures had no effect on, or inhibited epithelial cell growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the results presented here and those found previously (Lang et al, 1998) do not support this hypothesis. Our results, using a mixed population of stromal cells, would agree with both the theories that fibroblasts can stimulate (Kabalin et al, 1989;Gleave et al, 1991) or inhibit (Kooistra et al, 1995a;Degeorges et al, 1996) epithelial cell growth when compared to growth on tissue culture plastic. However, the majority of stromal cultures had no effect on, or inhibited epithelial cell growth.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro models have shown that primary cultures of prostatic stromal cells can stimulate epithelial growth derived from normal and malignant tissue (Kabalin et al, 1989) but also that prostate fibroblasts derived from normal and malignant tissue inhibit or have mixed effects on epithelial growth (Konig et al, 1987;Kooistra et al, 1995a;Degeorges et al, 1996). In vivo models indicate that whilst rat prostate tumour fibroblasts can stimulate LNCaP tumour cell growth, embryonic mouse fibroblasts had no effect (Camps et al, 1990;Gleave et al, 1991).…”
mentioning
confidence: 99%
“…Chung et al showed that IL-6 promoted cell growth of hormone-refractory cells but had no effect on the growth of hormone-dependent cell lines (4). Addition of exogenous IL-6 to the culture media of LNCaP cells by several groups has resulted in a dose-dependent inhibition of cell growth with development of a neuroendocrine cell phenotype (4,(18)(19)(20)(21)(22). On the other hand, some researchers observed a stimulatory response after treatment with IL-6 (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the favourable prognosis associated with the presence of tumour IL-6 in early-stage breast cancer (Karczewska et al, 2000) and the poor survival associated with high serum IL-6 levels in this series of metastatic breast cancer patients. It is noteworthy that, as in early-stage breast cancer, IL-6 functions as an inhibitor of cancer cell growth in benign prostate hyperplasia (Degeorges et al, 1996), but is correlated with a poor survival in stage-D prostate cancer (Nakashima et al, 2000).…”
Section: Prognostic Value Of Angiogenic Factors In Breast Cancer T Bamentioning
confidence: 99%